Secrets on Saturday - Purser, Ann (Sutton : Severn House, 2007)
Lois usually steers clear of local gossip, but after tidying up the house that newcomer Reg Abthorpe claims to have inherited, she has more suspicions than she can keep to herself. The home's previous resident was known for his beloved terrier, robust nature, and deficiency of living relatives. So why is Reg presenting himself as the old man's nephew-and where could the sprightly geriatric (and his dog) possibly have gone?
89157
Keywords: Meade, Lois (Fictitious character) -- Fiction; Cleaning personnel -- England -- Fiction; Country life -- England -- Fiction; Detective and mystery stories